1971
DOI: 10.1111/j.1365-2672.1971.tb01019.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Long Chain Fatty Acids and the Reversal with Calcium, Magnesium, Ergocalciferol and Cholesterol

Abstract: SUMMARY: Screening tests indicated that Gram positive bacteria are inhibited by long chain fatty acids. No inhibition was demonstrated with Gram negative bacteria. The minimum inhibitory concentrations (MIC) for a series of the fatty acids are presented. Growth curves in the presence of linolenic acid showed increases in lag phase duration and calcium addition reversed this effect, thus indicating the arbitrary nature of the MIC values. Bactericidal studies showed lauric acid to be the most active saturated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
166
2
6

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(188 citation statements)
references
References 22 publications
(5 reference statements)
14
166
2
6
Order By: Relevance
“…It has been demonstrated that lipids have a negative effect on bacterial growth. This action is more pronounced with PUFA than with SFA and is especially marked on cellulolytic strains (Galbraith et al, 1971). Another effect of fat supplementation is the decrease in the protozoal population, which contributes to cellulolysis (Doreau and Ferlay, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that lipids have a negative effect on bacterial growth. This action is more pronounced with PUFA than with SFA and is especially marked on cellulolytic strains (Galbraith et al, 1971). Another effect of fat supplementation is the decrease in the protozoal population, which contributes to cellulolysis (Doreau and Ferlay, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they attributed depressed cellulose digestion with lipids to a direct toxicity to cellulolytic bacteria. Because lack of colonization could also be due to the dramatically lowered bacterial numbers associated with toxicity of lauric and myristic acids (Galbraith et al 1971;Henderson 1973), it is not possible to determine if toxicity or detachment is responsible for the reduced digestibility associated with CO.…”
Section: Dietary Digestibilitymentioning
confidence: 99%
“…In pure culture, growth of Methanobacterium ruminantium is severely inhibited by long-chain fatty acids with the order of inhibitory activity of a series of long chain fatty acids being: C 18:1 >C 14 >C 12 >C 16 >C 18 (Prins et al 1972;Henderson 1973). The inhibitory pattern of long-chain fatty acids was similar for Gram-positive bacteria, but Gram negative bacteria were less sensitive to fatty acids at the same concentration (Galbraith et al 1971;Maczulak et al 1981).…”
mentioning
confidence: 99%
“…Many bacteria are sensitive to fatty acids. Unsaturated fatty acids, such as oleic acid, linoleic acid, and linolenic acid, are much more toxic than saturated fatty acids in bacteria (15,16). Unsaturated fatty acids disrupt the membrane structure in cells because of their distorted structures (17) and inhibit fatty acid-synthesizing enzymes (18).…”
mentioning
confidence: 99%